We are all only one pay cheque away from a life like this : experiences of unemployment and homelessness at a community shelter in Somerset West, Western Cape - Mordaunt-Bexiga, Michelle Mary (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.